Peran Teknologi Kecerdasan Buatan dalam Memahami Ayat-Ayat Pendidikan Al-Qur’an Secara Digital - Zainal Mustofa; Sayyid Syadad al-Hakim; Fauzan Sholeh (Sosaintek: Jurnal Ilmu Sosial Sains dan Teknologi, 2025)
The advancement of digital technology, particularly Artificial Intelligence (AI), offers new opportunities to support Islamic educational learning, including the understanding of Quranic verses related to education. This study aims to analyze the role of AI in facilitating the digital comprehension of Quranic educational verses and to identify its potential and limitations. A literature review method was employed, examining various journal articles, books, and prior research relevant to AI, Islamic education, and the Quran. The data were analyzed using a descriptive-analytical approach to provide an overview of AI's application in understanding educational verses. The findings indicate that AI can assist users in locating information, categorizing verse themes, simplifying material, and fostering more interactive learning. However, AI faces limitations regarding contextual understanding, information accuracy, and religious interpretation. Therefore, AI should be utilized as a learning aid, while verification through reliable exegesis sources and guidance from educators or experts remains essential.